PENGARUH UKURAN PERUSAHAAN DAN AKTIVITAS PERUSAHAAN TERHADAP SUSTAINABILITY REPORT DENGAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI (Studi pada Perusahaan LQ45 di Bursa Efek Indonesia Tahun 2014-2016) - Riskawati Nurul Maulidiyah, 16.05.62.0021; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and obtain empirical evidence about the effect of firm size and company activity on sustainability report with profitability as an intervening variable or mediation.The research sample consisted of 33 companies that went public on the Stock Exchange, where the method used was purposive sampling, namely the sampling method by setting certain criteria, namely LQ45 companies listed on the Indonesia Stock Exchange (IDX), respectively registered in the LQ45 sector of in 2014-2016, so that the pooled data method (2014-2016), obtained the number of observations (n) = 99. Data analysis method uses multiple regression with mediation or intervening. The results showed that there was no significant and positive effect between firm size on profitability, there was a significant and positive influence between activity on profitability, there was a significant influence between the size of the company and the sustainability report, there was a significant influence between activities on sustainability report, there is no significant effect between profitability and activity on sustainability report, profitability does not mediate the influence of firm size on sustainability report, and profitability doesn not mediate the effect of activity on sustainability report. Keywords: company size, company activity, profitability and sustainability report.